2018
DOI: 10.3389/fvets.2018.00120
|View full text |Cite
|
Sign up to set email alerts
|

International Survey Regarding the Use of Rehabilitation Modalities in Horses

Abstract: To define which biologic, electrophysical and other modalities are used in horses for injury or performance issues, a questionnaire regarding 38 modalities was distributed to eight veterinary groups. A total of 305 complete or partial responses were obtained from over 10 geographic regions; 75.4% from private equine practice or regional private equine referral hospitals, 14.1% from university teaching hospitals or satellite clinics, 8.2% from private mixed animal practice, and 2.3% from veterinary rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 27 publications
1
29
0
4
Order By: Relevance
“…In another survey of equine practitioners in 2018, PRP and ACS were considered two of the top 10 rehabilitation modalities for musculoskeletal injuries (12). PRP was used in 98.9% of cases to treat tendon or ligament injuries, while ACS was more frequently used in the joint postoperatively (55.3%) or to maintain performance (32.3%) (12). Similarly, in our survey, PRP and cellular therapies were more frequently used to treat soft tissue injuries (tendons or ligaments), while products such as ACS and APS were used to treat joint disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another survey of equine practitioners in 2018, PRP and ACS were considered two of the top 10 rehabilitation modalities for musculoskeletal injuries (12). PRP was used in 98.9% of cases to treat tendon or ligament injuries, while ACS was more frequently used in the joint postoperatively (55.3%) or to maintain performance (32.3%) (12). Similarly, in our survey, PRP and cellular therapies were more frequently used to treat soft tissue injuries (tendons or ligaments), while products such as ACS and APS were used to treat joint disease.…”
Section: Discussionmentioning
confidence: 99%
“…Equine practitioners have used NSIATs for years (12), and currently, there are many options available on the market. In the literature, there is limited information regarding the clinical experience of practitioners with these products, such as their product preference and treatment protocol (4,12). This survey was not a hypothesis-driven study.…”
Section: Introductionmentioning
confidence: 99%
“…At 6 and 12 months follow up, the foal did not have any deficits. In a survey of rehabilitation modalities used in horse treatments, massage was used by 69% of the respondents [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Guedes described manual therapy and movement as elective techniques in painful conditions but did not present any parameters of usage [ 37 ]. A survey published in 2018 indicated that range of motion therapies were reportedly used in 71.9% of the responses [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…There has been a recent proliferation of rehabilitation approaches and modalities with claims of effectiveness for treating musculoskeletal and neurological disorders in horses (Kaneps 2016; Schlachter and Lewis 2016; Wilson et al 2018b). There is also a growing body of evidence that some of these modalities do have a level of safety and efficacy in specific applications (Nankervis et al 2016; Haussler 2018; Holcombe et al 2019).…”
Section: Introductionmentioning
confidence: 99%